Enhancing the evaluation process of sustainability related criteria in Malaysia landfill site selection - Tey, Jia Sin (2019)
Landfilling is the ultimate waste management system in Malaysia. However, based on the summary report by Department of National Solid Waste Management in Malaysia, out of 161 operating landfills, there are only 16 sanitary landfills, which means more than half of the landfills are posing serious effects to the environment and public health. The selection of a landfill site is often a disturbing issue where imprudent selection may leave negative impacts to the surrounding environment, social, and economic value of the land. It is known that landfill site selection is extremely difficult as it depends on many factors and regulations. To date, the existing landfill site selection guideline is found to be deficient especially in engaging with sustainable-related concepts. Therefore, this research is aimed at producing a decision-making guideline in enhancing its sustainability during landfill site selection. This research probed into the perceptions of the stakeholders towards sustainable deliverables in a landfill site selection project, identified the sustainability related criteria and developed the sustainability related model. The study is carried out with mixed-method approach where the interviews with nineteen respondents and questionnaire surveys with seventy respondents were performed. All the respondents are the industry stakeholders involved in the landfill site selection. The qualitative result was analysed through the Nvivo software while the quantitative result was obtained using Partial Least Square Structural Equation Modelling (PLS-SEM) tool as well as Statistical Package for the Social Sciences (SPSS). The result of the interview has substantiated the lack of understanding towards the sustainability concept incorporated in the landfill site selection. The results of the quantitative analysis reveal that all the sustainable criteria play an important role in landfill site selection. However, the economy and social aspects having higher effect compare to the environmental. All of the identified sustainable criteria were integrated into the model. This model is vital in enhancing the sustainable concept during the evaluation of the landfill site selection. This model also plays an important role in improving the existing guideline so that the evaluation process of landfill site selection could become more sustainable especially for the government agencies and industry stakeholders in Malaysia. The outcome of this study fills the gap in landfill site selection by integrating the concept of sustainability in the landfill site selection project in Malaysia.